138k views
0 votes
The expression the quantity 1 plus tangent x end quantity over the quantity 1 minus tangent x end quantity can be rewritten as which of the following

The expression the quantity 1 plus tangent x end quantity over the quantity 1 minus-example-1
User JimiLoe
by
6.1k points

1 Answer

0 votes

The identity for a tangent of the subtraction of two angles is:


\tan (\theta-x)=(\tan(\theta)-\tan(x))/(1+\tan(\theta)\cdot\tan(x))=(-\tan(\theta)+\tan(x))/(-1-\tan(\theta)\cdot\tan(x))

Then, given the expression:


(1+\tan(x))/(-1+\tan(x))

We identify:


\begin{gathered} \tan (\theta)=-1 \\ \Rightarrow\theta=(3\pi)/(4) \end{gathered}

We conclude that:


(1+\tan(x))/(-1+\tan(x))=\tan ((3\pi)/(4)-x)

User Kila
by
6.2k points